Political Trust in the American States. (March 2015) - Weinschenk, Aaron C.; Helpap, David J.
This article illustrates that trust in state government varies considerably across states. Using newly available public opinion data, the authors investigate the effects of political polarization, corruption, income inequality, unemployment, state fiscal conditions, median income, ideology, state size, tax rates, and social capital on differences in trust in state government. A number of these variables have statistically significant effects on trust in state government, including state fiscal conditions, unemployment, state ideology, and corruption. The article concludes with a discussion of the implications of the findings for policy makers and elected officials.